Calculation the Fast Neutrons Interaction Parameters for Several Carbohydrates - Abdullah, Kalyan Hama Salih; Mahmod , Sabah A (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
The investigation of fast neutron removal cross section ∑R and mean free path have been studied in this work for some carbohydrates which affected on the living cells. The carbohydrates included (Arabinose, Ribose, Glucose, Mannose, Fructose, Maltose, Sucrose, Lactose, Lactose monohydrate, Melezitose and Raffinose) have different densities so, they have different removal cross section. The study was implemented by the mass removal cross section ∑R/ρ data for carbohydrate composition. ∑R and ∑R/ρ have been calculated by using empirical equations program with python 3.10.11 language for all carbohydrates. The calculation results, show that Ribose has the minimum value removal cross section, while Fructose has the maximum value of removal cross section, and all the results are in reasonable corresponding.